INTERAKSI SOSIAL DAN PESAN BUDAYA SEBAGAI LANDASAN PENDIDIKAN - Lestari, Dewi (Lentera: Jurnal Ilmiah Kependidikan, 2019)
This paper aims at outlining the elements that can affect the socio-cultural education and explain how social interactions and cultural messages that can affect educational foundation. The importance of conducting sociocultural interactions is a means or tool in the learning process at school. Learning based on the cultural and social interaction refers to the development of higher mental functions and associated with historical socio-cultural aspects. These will be very affects perception, memory and thinking of children. Social and cultural interactions can affect a person's way of thinking and interacting. Contributions culture of each child if it can be accommodated properly by teachers will have its own power as the strength of the culture is rooted in the community.